Chain dynamics and crystalline network structure of poly[R-3-hydroxybutyrate-co-4-hydroxybutyrate] as revealed by solid-state NMR. Issue 15 (24th March 2021) - Xia, Zhijie; Zhao, Haoyuan; Wang, Yusong; Ma, Yiming; Wang, Xiaoliang; Meng, Lingpu; Wang, Daoliang; Sheng, Junfang; Chen, Wei
Abstract : The chain dynamics and crystalline network structure of poly[ R -3-hydroxybutyrate- co -4-hydroxybutyrate] (P(3HB- co -4HB)) were systematically investigated by the combination of various solid-state NMR techniques. Abstract : The chain dynamics and crystalline network structure of poly[ R -3-hydroxybutyrate- co -4-hydroxybutyrate] (P(3HB- co -4HB)) were systematically investigated by the combination of various solid-state NMR techniques. High-resolution 13 C cross-polarization (CP) and direct-polarization (DP) MAS with selective recycle delay times were first used to check the presence or absence of the 4HB unit in the crystalline domain. The results show that the 4HB unit is excluded from the crystalline domain. Afterward, 1 H MAS Nuclear Overhauser Effect Spectroscopy (NOESY) with different mixing times was used, which shows that no micro-phase separation exists in the amorphous domain. 1 H magic-sandwich-echo (MSE)-FID at elevated temperature shows the absence of motions on a timescale of 100 μs and below in the crystalline domain, as evidenced by the invariant second moment M 2 of the proton line shape. Finally, the crystalline based network density was characterized directly by magic and polarization echo (MAPE)-double quantum (DQ) NMR, which shows a significant decreasing tendency after 80 °C. Such a decreasing crystalline network density, together with the reduced relaxation time, results in the significant decrement of the maximum stretch ratio and modulus in the high-temperature region.